EARLY INTERVENTIONS FOR PTSD: A REVIEW - Kearns, Megan C.; Ressler, Kerry J.; Zatzick, Doug; Rothbaum, Barbara Olasov (Depression and anxiety, 2012)
The high prevalence of trauma exposure and subsequent negative consequences for both survivors and society as a whole emphasize the need for secondary prevention of posttraumatic stress disorder. However, clinicians and relief workers remain limited in their ability to intervene effectively in the aftermath of trauma and alleviate traumatic stress reactions that can lead to chronic PTSD. The scientific literature on early intervention for PTSD is reviewed, including early studies on psychological debriefing, pharmacological, and psychosocial interventions aimed at preventing chronic PTSD. Studies on fear extinction and memory consolidation are discussed in relation to PTSD prevention and the potential importance of immediate versus delayed intervention approaches and genetic predictors are briefly reviewed. Preliminary results from a modified prolonged exposure intervention applied within hours of trauma exposure in an emergency room setting are discussed, along with considerations related to intervention reach and overall population impact. Suggestions for future research are included. Prevention of PTSD, although currently not yet a reality, remains an exciting and hopeful possibility with current research approaches translating work from the laboratory to the clinic.